The Influence of Leadership and Organizational Culture on Employee Performance Through Employee Loyalty at the Prestasi Cendikia Foundation, Bekasi - Yahya, Surono; Ali, Hapzi; Sasanti Munir, Ningky (Dinasti Publisher, 2024)
The aim of this research is to analyze the influence of leadership and organizational culture on performance through employee loyalty at the Bekasi Prestasi Cendikia Foundation.